2010
DOI: 10.1186/1471-2458-10-316
|View full text |Cite
|
Sign up to set email alerts
|

The impact of food assistance on weight gain and disease progression among HIV-infected individuals accessing AIDS care and treatment services in Uganda

Abstract: BackgroundThe evidence evaluating the benefits of programmatic nutrition interventions to HIV-infected individuals in developing countries, where there is a large overlap between HIV prevalence and malnutrition, is limited. This study evaluates the impact of food assistance (FA) on change in weight and disease progression as measured by WHO staging.MethodsWe utilize program data from The AIDS Support Organization (TASO) in Uganda to compare outcomes among FA recipients to a control group, using propensity scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
56
0
7

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 21 publications
16
56
0
7
Order By: Relevance
“…To discourage this practice among Malawian food-insecure households, several authors have suggested considering counselling activities in health-care facilities and/or integrating HIV care in safety net programmes (7) . The importance of integrating nutrition programming in the standard care of PLHIV to relieve food insecurity, improve their nutritional status and overall health has been also underscored by other authors (7,33,34) . In addition, the combination of distribution of the special nutritious food for PLHIV together with household food assistance (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…To discourage this practice among Malawian food-insecure households, several authors have suggested considering counselling activities in health-care facilities and/or integrating HIV care in safety net programmes (7) . The importance of integrating nutrition programming in the standard care of PLHIV to relieve food insecurity, improve their nutritional status and overall health has been also underscored by other authors (7,33,34) . In addition, the combination of distribution of the special nutritious food for PLHIV together with household food assistance (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…21 The goal is to find out whether combining MCHN and sanitation interventions, for example, results in greater impact than could be achieved by introducing either intervention set alone. To do so, a reference case of no participation in either intervention is compared with three alternatives: (1) participation in 16 See Rawat, Kadiyala and McNamara (2010) for an example of another study that relies on sub-groups of project participants for intervention-specific control groups to evaluate a multi-intervention project.…”
Section: Methods For Investigating Why the Project Impacted Stuntingmentioning
confidence: 99%
“…[31][32][33][34][35][36] The model begins with propensity score matching, which ensures that the observed characteristics of the intervention and matched control group are comparable, consequently eliminating as much observed heterogeneity as possible. 37 Because the matched control group provides a counterfactual for the intervention group had there been no intervention, the difference-in-differences part of the model removes unobserved heterogeneity that was fixed over time or that followed parallel time trends between groups, thus providing a robust estimator.…”
Section: Discussionmentioning
confidence: 99%